LEVEL IMAJINASI MATEMATIS SISWA SMP - Novi Andri Nurcahyono, - (2021)
This study aims to obtain a description of the level of mathematical imagination of junior high school students in solving mathematical problems. The research method was a qualitative research method with grounded theory design. The research subjects consisted of 8 students who were selected purposively based on test results and consultation with the mathematics teacher. Data collection techniques used tests, observation, and interviews. The results of the analysis obtaine several conclusions, namely: 1) Indicators of junior high school students' mathematical imagination are sensibility, intuition, crystallization, transformation, exploration, elaboration, productivity, effectiveness, and novelty; 2) The level of junior high school students' mathematical imagination, namely, initiating imagination, conceiving imagination, analyzing imagination and developing imagination; 3) Characteristics of the level of initiating imagination, namely the reception of information begins with impressions and feelings, occurs spontaneously, generates intuition, captures and interprets information, emerges decisions quickly, and is based on experiences that have been experienced. The characteristics of the conceiving imagination level are using real examples, making sketches, making brief conclusions, compiling plans, emerging new concepts, and identifying various data. The characteristics of the level of analyzing imagination are exploring, forming a general, detailed, thorough, diligent and careful understanding, studying new experiences/situations, gathering information, exploring, observing, and analyzing, reasoning, drawing conclusions, developing/enriching ideas, and steps. detailed steps. Characteristics of the level of developing imagination are generating many ideas, using resources, successful actions, and unusual ideas; 4) The obstacles that arise are failure to capture and interpret the information in the problem and fail to paying close attention and analyzing the various possibilities of the existing information, fail to making a sketch, fail to find an association between the information and the sketch that is made by solving problems, fail to understanding the concept, failing in searching and exploring to find solutions to problems, inaccurate in using knowledge in solving problems, not being diligent and careful in processing, misconceptions, failing in analyzing and exploring how to solve them, and failing to analyze and form a general understanding of the phenomena found, failing in obtaining conclusions and failing in studying in detail and examining and investigating thoroughly the results obtained; 5) Inhibiting factors in bringing up mathematical imagination, namely, cognition, motivation, self-confidence, and inspiration.